Indirect measurements of neutron cross-secti at heavy-ion storage rings. (October 2020) - Henriques, A.; Jurado, B.; Grieser, M.; Denis-Petit, D.; Chiron, T.; Gaudefroy, L.; Glorius, J.; Langer, C.; Litvinov, Yu. A.; Mathieu, L.; Méot, V.; Pérez-Sánchez, R.; et al.
Abstract: Cross sections for neutron-induced reactions of short-lived nuclei are essential for nuclear astrophysics since these reactions in the stars are responsible for the production of most heavy elements in the universe. These reactions are also key in applied domains like energy production and medicine. Nevertheless, neutron-induced cross-section measurements can be extremely challenging or even impossible to perform due to the radioactivity of the targets involved. Indirect measurements through the surrogate-reaction method can help to overcome these difficulties. The surrogate-reaction method relies on the use of an alternative reaction that will lead to the formation of the same excited nucleus as in the neutron-induced reaction of interest. The decay probabilities (for fission, neutron and gamma-ray emission) of the nucleus produced via the surrogate reaction allow one to constrain models and the prediction of the desired neutron cross sections. We propose to perform surrogate reaction measurements in inverse kinematics at heavy-ion storage rings, in particular at the CRYRING@ESR of the GSI/FAIR facility. We present the conceptual idea of the most promising setup to measure for the first time simultaneously the fission, neutron and gamma-ray emission probabilities. The results of the first simulations considering the 238 U(d, d') reaction are shown, as well as new technical developments that are being carried out towards this set-up.